Biodiversity of New Lytic Bacteriophages Infecting Shigella spp. in Freshwater Environment - Shahin, Khashayar; Barazandeh, Mohadeseh; Zhang, Lili; Hedayatkhah, Abolghasem; He, Tao; Bao, Hongduo; Mansoorianfar, Mojtaba; Pang, Maoda; Wang, Heye; Wei, Ruicheng; Wang, Ran (Frontiers in Microbiology, 2021)
Bacteriophages, viruses that infects and replicates within prokaryotic cells are the most abundant life forms in the environment, yet the vast majority of them have not been properly reported or even discovered. Almost all reported bacteriophages infecting the Enterobacteriaceae family, with E. coli being the major subject of studies, have been isolated from wastewater, sewage, and effluent resources. In the present study we focused on the distribution and biodiversity of Shigella phages in an aquatic ecosystem. While no Shigella bacteria was recovered from the Yangtze River, three lytic phages were isolated from this ecosystem and were subjected to biological, morphological, and genomic characteristics. Comparative genomics and phylogenetic analyses demonstrated that vB _SflM_004 isolate belongs to Myoviridae family, Felixounavirus genus of Ounavirinae subfamily, vB_SdyM_006 was classified under the same family, however, it is suggested to be in a new genus under Tevenvirinae subfamily with some other related bacteriophages. vB_SsoS_008 phage belongs to the Siphoviridae family, Tunavirus genus, Tunavirinae subfamily. The phages did not harbor any genes involved in the lysogenic cycles, and showed a high temperature and pH stability. The biodiversity of the isolated phages highly suggests that continued isolation on non-model members of Enterobacteriaceae family is necessary to fully understand bacteriophage diversity in aquatic environments.